Optimasi Sistem Pencahayaan pada Ruang Kelas SDN Pinang 03 - Kiki Setiawan; M. Rafli Fadillah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Classroom 4.3.4, 5.3.2 and 6.3.3 is used as a classroom for teaching and learning at SDN PINANG 03. The focus of discussion in this study is the illumination and lighting systems in the classroom. Illumination that occurs in the classroom does not meet standards, illumination for classroom lighting is 250 lux - 300 lux, the amount of light points is not in accordance with the standard calculation, finding some space with lighting installations are not designed in groups. One attempt to correct this condition is to make proposals optimization. The first optimization is to replace the existing types of lamps with 36 watt fluorescent lamp, with the number of lights installed at each point lights (luminaire) by 2 pieces and the number of points of light used is the number of point lights existing condition. The second optimization is to use the same type of lights to the existing condition is a downlight Philips Essential 23W Energy Saver E27 220-240V 50-60 Hz Cool Daylight lamp with a number of points based on standard calculations. The third optimization is to replace the existing types of lamp with 36 watt fluorescent lamp with a number of lights installed at each point lights (luminaire) by 2 pieces and the number of light points in accordance with accounting standards. The study was done by measuring the strong lighting in the classroom by means of a lux meter, analyze case studies on existing conditions with the theory. Then the results of these measurements will be compared with the illumination calculations in accordance with the standard formula, which in turn will get to do some optimization. The results of this study showed a strong improvement of the optimization of the value nearing illumination standards and meet the standards. Optimizations that meet the standards is the third optimization with a illumination value on classroom 4.3.4 is 257 lux , classroom 5.3.2 is 278 lux and classroom 6.3.3 is 317 lux. Values obtained from this optimization are powerful illumination range of 257 lux to 317 lux. It can be concluded that the results of this optimization meet strong standards for classroom lighting.